Pengembangan Perangkat Pembelajaran Matematika Berbasis Guided Discovery Untuk Meningkatkan Kemampuan Problem-Solving Peserta Didik Kelas VIII SMP/MTS - Safitri, Winda; Syarifuddin*, Hendra; Musdi, Edwin; Asmar, Ali (JEMS: Jurnal Edukasi Matematika dan Sains, 2022)
A good learning tool is one of the important things to make. This is because the support of learning devices also affects the achievement of a directed learning process so that mathematics learning is also achieved, such as solving mathematical problems. The ability to solve mathematical problems is expected to develop well in each student. Based on this, it is necessary to develop guided discovery-based learning tools to improve students' problem-solving skills. The research was conducted with the aim of knowing the characteristics of guided discovery-based learning that are valid, practical and effective to improve the problem-solving abilities of eighth grade students of SMP/MTs. This type of research is using the Plomp model, which consists of three stages, namely the preliminary stage, the prototype stage and the assessment stage. The instruments in this study were validation sheets, observation sheets, questionnaires, interviews and tests. The results showed that the learning tools in the form of RPP and LKPD based on guided discovery for class VIII SMP/MTs were valid, practical, and effective. The validity of the RPP reached 79% and LKPD 80.2%. While the practicality of the lesson plans is 77.6% and LKPD 90.5%. In addition, the effectiveness of the two products to improve problem solving skills is 83.87%.